Stephanofilariasis in beef cattle-case report - Schade J. (2019)
© 2019, Universidade Federal de Minas Gerais.Stephanofilariasis is an ulcerative dermatitis caused by nematodes that affect cattle in several countries in the world. However, it has not been described in beef cattle in Brazil. The objective of this study is to describe three cases of stephanofilariasis, which occurred in beef cows in the municipality of Ipe, RS, Brazil. The disease was characterized by pruritic, ulcerated and crusty seasonal lesions present in the cranial region of the udder. The diagnosis was confirmed by analyses of secretions stained smears and by direct optical microscopic examination of the sediment and the treatment was effectively carried out with topical trichlorphon. This report indicates that stephanofilariasis should be included as a differential diagnosis for dermatopathies in beef cattle in Brazil.